2015
DOI: 10.1016/j.carbon.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the hydrogen and oxygen gas pressure dependence of the tribological properties of silicon oxide–doped hydrogenated amorphous carbon coatings

Abstract: Silicon oxide-doped hydrogenated amorphous carbons (a-C:H:Si:O) are amorphous thin films used as solid lubricants in a range of commercial applications, thanks to its increased stability in extreme environments, relative to amorphous hydrogenated carbons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 37 publications
4
55
0
2
Order By: Relevance
“…In addition, although Ar and N 2 are both chemically inert, the tribological behaviors of a-C:H lms are different in these two atmospheres. 33,35,44 Usually, a-C:H lms have higher COFs in dry Ar gas environment (Table 1). Fontaine et al found that the wear life of a-C:H lm under vacuum is very short, only 40 times.…”
Section: Tribological Behaviors Of A-c:h Lmmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, although Ar and N 2 are both chemically inert, the tribological behaviors of a-C:H lms are different in these two atmospheres. 33,35,44 Usually, a-C:H lms have higher COFs in dry Ar gas environment (Table 1). Fontaine et al found that the wear life of a-C:H lm under vacuum is very short, only 40 times.…”
Section: Tribological Behaviors Of A-c:h Lmmentioning
confidence: 99%
“…The major difference between these two environments is their thermal conductivities. Under ultrahigh vacuum, the temperatures of the contacting surfaces are approximately 100-200 C higher than in dry inert gas atmosphere, 44 perhaps causing the shorter wear life of a-C:H lms under ultra-high vacuum than in dry Ar gas environments.…”
Section: Electronic Interactions Mechanismmentioning
confidence: 99%
“…The structural instability of the hydrogen bonds under high temperatures causes the breaking of chemical bonds, the removal of hydroxyl radicals, and the release of a large amount of crystal water and reactive oxygen. The resulting expansion of the specific surface area and increase in chemical activity of the nanometer lanthanum borate [17][18][19], on the one hand, activate the catalytic performance of the rare-earth element La, resulting in the boronization between the B and Fe base [11], the formation of FeB film (lowbinding energy), and the effective reduction in contact force and abrasive wear [20]. On the other hand, they help with the formation of an La2O3 oxidation film between La and reactive oxygen, which compensates for the surface wear and thus reduces friction and wear.…”
Section: Discussion Of the Anti-friction And Anti-wear Mechanismmentioning
confidence: 99%
“…The introduction of silicon and oxygen in a‐C:H:Si:O was, however, found to drastically increase the thermo‐oxidative resistance through the formation of a thin silica surface layer, which prevents the underlying carbonaceous phase to be eroded. a‐C:H:Si:O films also exhibit low wear and friction over a wider range of environmental conditions compared to undoped a‐C:H . It has also been shown to have high resistance to wear under high‐stress nanoscale sliding .…”
mentioning
confidence: 99%
“…A detailed description of the experimental methods is reported in the Supporting Information. Characterization of the commercial PECVD a‐C:H:Si:O has been previously reported …”
mentioning
confidence: 99%